Pentingnya Penghargaan terhadap Nilai Kearifan Lokal: Analisis Filosofis atas Kasus Pembakaran Mahkota Cenderawasih di Jayapura - Edi Supriyanto; Fabylio Cornelius Togas; Liberatus Welerubun; Paulus Kus Bukan; Yohanis Resubun; Anselmus Jamlean (Jurnal Seri Mitra (Refleksi Ilmiah Pastoral), 2026)
Every community group has a collective appreciation for objects that hold deep indigenous wisdom (local wisdom), including the Papuan indigenous community regarding the crown of the Bird of Paradise (Cenderawasih). This research aims to provide an accurate review of the Cenderawasih crown burning case in Jayapura and to offer a relevant philosophical assessment. The core question posed by the author is what is the appropriate analysis of the Cenderawasih crown burning issue in Jayapura, especially when viewed from a philosophical perspective. Through qualitative research utilizing a descriptive-analytical writing method, the author found that a violation of local wisdom values occurred through this Cenderawasih crown burning case. The action taken by the BBKSDA (Papua Natural Resources Conservation Agency) was intended to deter individuals involved in the illegal hunting of the Cenderawasih, an endangered endemic bird , but on the other hand, the act of burning they chose sparked protests from the Papuan community, who viewed it as a disregard for their customs and traditions. Therefore, a precise assessment from a philosophical standpoint is needed to avoid bias in evaluating this case